Enhancing microwave absorption performance of MoS2 by synergistic effect of Fe doping - Yuefeng Yan; Guangyu Qin; Kaili Zhang; Boshi Gao; Guansheng Ma; Xiaoxiao Huang; Yu Zhou (Journal of Advanced Ceramics)
Owing to its unique two-dimensional structure and tunable electronic properties, MoS2 has emerged as a promising electromagnetic wave (EMW)-absorbing material that can be extensively combined with various other substances to construct effective EMW absorbers. However, research on cation substitution doping in MoS2 remains relatively limited, which impedes the design and development of high-performance MoS2-based EMW absorbing materials. In this study, MoS2 was synthesized with various concentrations of doped Fe via a facile hydrothermal method. We thoroughly investigated the effects of Fe doping, which induced lattice distortion and collapse, triggered a 1T‒2H phase transition, and led to the formation and evolution of second phases. The modulation of phase transitions, coupled with doping-induced lattice defects that enhance polarization and interfacial polarization from second phases, enabled the Fe-doped MoS2 samples to exhibit remarkable EMW absorption performance. Notably, the sample FM3 achieved an effective absorption bandwidth (EAB) of 5.1 GHz and a minimum reflection loss (RLmin) of −60.6 dB, underscoring the critical role of Fe doping in increasing the EMW absorption ability. This research provides valuable pathways and unique insights for the advancement of transition metal dichalcogenides (TMDs) as high-performance EMW-absorbing materials.